2000
DOI: 10.1074/jbc.m005643200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitochondria in the Regulation of Hypoxia-inducible Factor 1 Expression during Hypoxia

Abstract: Hypoxia-inducible factor 1 (HIF-1) is a heterodimeric transcription factor that regulates transcriptional activation of several genes responsive to the lack of oxygen, including erythropoietin, vascular endothelial growth factor, glycolytic enzymes, and glucose transporters. Because the involvement of mitochondria in the regulation of HIF-1 has been postulated, we tested the effects of mitochondrial electron transport chain deficiency on HIF-1 protein expression and DNA binding in hypoxic cells. The neurotoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
2
7

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(149 citation statements)
references
References 31 publications
9
131
2
7
Order By: Relevance
“…Both molecules accumulated following exposure of normoxic cells to cobalt chloride and desferrioxamine. Previous results reported mitochondrial reactive oxygen species inhibitors such as DPI, rotenone and myxothiazol dramatically reduced hypoxia-induced HIF-1α accumulation and basal activity [21,43]. In the present study, we found that all the three radical scavengers partially abolished the basal and hypoxic induction of HIF-3α and HIF-1α protein.…”
Section: Discussionsupporting
confidence: 74%
“…Both molecules accumulated following exposure of normoxic cells to cobalt chloride and desferrioxamine. Previous results reported mitochondrial reactive oxygen species inhibitors such as DPI, rotenone and myxothiazol dramatically reduced hypoxia-induced HIF-1α accumulation and basal activity [21,43]. In the present study, we found that all the three radical scavengers partially abolished the basal and hypoxic induction of HIF-3α and HIF-1α protein.…”
Section: Discussionsupporting
confidence: 74%
“…40 Initial studies implicating the electron transport chain in HIF-1a stabilization have demonstrated that certain inhibitors of the electron transport chain, including rotenone (which inhibits complex I distally), myxothiazol, and stigmatellin (which inhibit complex III) block the hypoxic stabilization of HIF-1a. [41][42][43] Genetic deletions of complex I, likewise, blocked HIF-1a stabilization. 44 Finally, cells depleted of their mitochondrial DNA by incubation with low levels of ethidium bromide (known as rho-zero cells) fail to stabilize HIF-1a in response to hypoxia.…”
Section: Regulation Of Hif Functionmentioning
confidence: 94%
“…The precise mechanism linking oxygen depletion to HIF-1 activity is an area of avid research. Perturbations of the mitochondrial respiratory chain under hypoxia have been implicated (Chandel et al, 1998(Chandel et al, , 2000Agani et al, 2000). However, this is contentious, and HIF-1 activation under hypoxia has been demonstrated in cells lacking the mitochondrial respiratory chain electron transport pathway (Srivanas et al, 2001).…”
Section: Introductionmentioning
confidence: 99%